Kontroversi Hadis sebagai Sumber Hukum Islam - Wahyudin Darmalaksana; Lamlam Pahala; Endang Soetari (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2017)
The position of hadith as the source of Islamic law has brought about a problematic long debate between the denial and the defender of hadith. The problemes surrounding the hadith's position concerns the hadith in the aḥad category which is contrasted with the mutawtir category. This study aims to analyze the position of hadith as a source of Islamic law. This researcāh uses qualitative research method through literature study by using a content analysis methode to obtain a conclusion. The discussion of this study presents the arguments surrounding hadith as the source of Islamic law among its denials and defenders. The denial of the hadith takes the ijtihād rather than positioning the aḥad hadith as the source of Islamic law. Thus, the defenders of hadith from the experts of hadith still insist on asserting hadith as the source of Islamic law even though it is a category of aḥad by developing a systematic methode of hadith research. This study concludes that the problemes surrounding the position of hadith as a source of Islamic law have given rise to positive dynamics for the development of the methodology of hadith research.